2014 IEEE International Conference on Data Mining 2014
DOI: 10.1109/icdm.2014.136
|View full text |Cite
|
Sign up to set email alerts
|

Locally Estimating Core Numbers

Abstract: Abstract-Graphs are a powerful way to model interactions and relationships in data from a wide variety of application domains. In this setting, entities represented by vertices at the "center" of the graph are often more important than those associated with vertices on the "fringes". For example, central nodes tend to be more critical in the spread of information or disease and play an important role in clustering/community formation. Identifying such "core" vertices has recently received additional attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…It has been shown that ego networks in real-world networks exhibit low conductance [15] and also can be used for friend suggestion in online social networks [11]. Accurate and fast estimation of core numbers [29] is important in the context of network experiments (A/B testing) [43] where a random subset of vertices are exposed to a treatment and responses are analyzed to measure the impact of a new feature in online social networks.…”
Section: Partialand To Estimate κ2 and κ3 Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that ego networks in real-world networks exhibit low conductance [15] and also can be used for friend suggestion in online social networks [11]. Accurate and fast estimation of core numbers [29] is important in the context of network experiments (A/B testing) [43] where a random subset of vertices are exposed to a treatment and responses are analyzed to measure the impact of a new feature in online social networks.…”
Section: Partialand To Estimate κ2 and κ3 Valuesmentioning
confidence: 99%
“…Previous attempts to find the approximate core numbers (or k-cores) focus on the neighborhood of a vertex within a certain radius [29]. It is reported that if the radius is at least half of the diameter, close approximations can be obtained.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, according to Eq. 4, the status change from √ to × for v ′ will trigger each neighbor u ′ of v ′ to decrease its cnt(u ′ ) if status(u ′ ) = √ (line [24][25]. For each such u ′ , if cnt(u ′ ) is decreased below c old , status(u ′ ) need to be updated in the same of later iterations (line [26][27].…”
Section: Optimization For Edge Insertionmentioning
confidence: 99%
“…Core decomposition in an uncertain graph is studied in [10]. Locally computing and estimating core numbers are studied in [12] and [24] respectively. [27] and [19] propose in-memory algorithms to maintain the core numbers of nodes in dynamic graphs.…”
Section: Related Workmentioning
confidence: 99%
“…In the original definition of k-core, Seidman states that k-core is the maximal and connected subgraph where any vertex has at least degree k [43]. However, almost all the recent papers on k-core algorithms [8,18,19,6,36,32,28,52,51,32] did not mention that k-core is a connected subgraph although they cite Seidman's seminal work [43]. On the k-truss side, the idea is introduced independently by Saito et al [39] (as k-dense), Cohen [10] (as k-truss), Zhang and Parthasarathy [56] (as triangle k-core), and Verma and Butenko [47] (as k-community).…”
Section: Problem Misconception and Challengesmentioning
confidence: 99%